REPRESENTASI PATRIARKI DALAM FILM “YUNI” - Nadya Febiola; Agusly Irawan Aritorang; Daniel Budiana (Institute of Research and Community Outreach - Petra Christian University, 2022)
Patriarchy in Indonesia is still strong, as can be seen from high cases violence against women. Patriarchy occurs from the presence of gender differences. This research is made to discover how patriarchy is represented in the movie ‘Yuni’. ‘Yuni’ is a movie with the setting taken in Serang, West Java, produced by FourColor Films. The movie ‘Yuni’ reveals the practice of patriarchy in everyday life in Indonesia. The type of research used is descriptive qualitative, using a semiotic analysis method by Roland Barthes with scenes from ‘Yuni’ film as the subject of research and analyzed representation of patriarchy in the film ‘Yuni’ as the object of research. The research results in showing that patriarchy is implemented through religion and culture, and that the cause of patriarchy is materialism. Furthermore, 5 aspects such as patriarchy controls women's sexuality, patriarchy limits women's education, patriarchy limits women's job in the domestic sphere, patriarchy encourages early marriage and patriarchy limits women's movement and rights.